Association between allergic diseases and ophthalmologic diseases, including cataracts and glaucoma, using the Korean National Health and Nutrition Examination Survey 2010–2012: A STROBE‐compliant article. Issue 4 (4th January 2018) - Lee, Young Bok; Lee, Ji Hyun; Kang, Min Ji; Choi, Jin Young; Kim, Jin‐Wou; Yu, Dong Soo; Han, Kyung Do; Park, Yong Gyu
Abstract: This study investigated the association between allergic diseases and comorbid ophthalmologic diseases. We enrolled 14 776 participants who were at least 19 years of age. Multiple logistic regression analyses were used to evaluate the odds ratios for cataracts and glaucoma according to the presence of allergic diseases. Atopic dermatitis was not associated with the development of cataracts and glaucoma. However, asthma and allergic rhinitis were significantly associated with cataracts (hazard ratio [HR] = 1.511, 95% confidence interval [CI] = 1.120–2.039 and HR = 1.565, 95% CI = 1.192–2.054, respectively). This study examined a nationwide, population‐based survey, and concluded that cataracts were significantly associated with asthma and allergic rhinitis but not with atopic dermatitis. Efforts should be made to reduce the risk of ophthalmologic complications when treating patients with allergic diseases.